Adaptive Managerial Strategies in Schools During the Digital Disruption Era to Foster Innovative Learning Environments - Pettalongi, Sagaf S; Lopulalan, Pierre Marcello; Gunawan, Adriani (Asian Journal of Applied Education (AJAE), 2025)
This study analyzes adaptive managerial strategies adopted by high schools in responding to digital disruption, focusing on leadership policies and management practices that foster creative, collaborative, and technology-based learning environments. Using a qualitative case study approach involving 12 informants from three schools in Palu City, data were collected through interviews, observations, and document analysis, then examined using thematic analysis. The findings reveal that key adaptive strategies include strengthening digital leadership, enhancing teacher competence through continuous training, optimizing online learning platforms, and cultivating a culture of collaboration and innovation. The study concludes that school success amid digital disruption depends on flexible, responsive, and visionary management, contributing to adaptive education management theory and offering practical guidance for developing sustainable, innovation-driven learning ecosystems.